Concerning Criteria for transfer of Attenuated Yersinia pestis strains from Pathogenicity (Hazard) Group I into Pathogenicity Group III - S. V. Dentovskaya; A. S. Trunyakova; A. S. Vagaiskaya; M. E. Platonov; E. A. Tyurin; A. P. Anisimov (Проблемы особо опасных инфекций, 2022)
Live vaccines induce both cellular and humoral immunity and are cheap and easy to use. The induction of immunity is provided through the reproduction of the vaccine strain in the host body without the development of the disease, since the bacterium to which it is necessary to induce the immunity is characterized by reduced virulence (attenuation). The first generation of attenuated strains was chosen from a variety of spontaneous or physically, chemically and biologically induced mutants after virulence assessment. The rapid development of molecular genetics makes it possible to significantly reduce the time of pathogen attenuation via obtaining knockout mutants with genes selected by a researcher or by inserting “avirulence genes” into the genome. But, given that the methodological aspects of the design of avirulent strains are basically clarified, the absence of officially established criteria for assessing the hazard in regulatory documents hinders the determination of the degree of attenuation. In this regard, there is a need for changes in the procedure for accounting and storage of bacterial cultures, as well as regulation of the process of transferring plague pathogen avirulent strains from the 1st into the 3rd pathogenicity group for subsequent use in the vaccine preparations development. Thereat, the requirements to methodological aspects of the safe generation of attenuated Yersinia pestis strains and the criteria for testing the virulence loss should be maintained at high levels